2023
DOI: 10.1177/15347354231162080
|View full text |Cite
|
Sign up to set email alerts
|

The Herbal Medicine Suanzaoren (Ziziphi Spinosae Semen) for Sleep Quality Improvements: A Systematic Review and Meta-analysis

Abstract: Background: Sleep disturbances are common and bothersome among cancer and noncancer populations. Suanzaoren ( Ziziphi Spinosae Semen) is commonly used to improve sleep, yet its efficacy and safety are unclear. Methods: We systematically searched PubMed, Cochrane Library, and EMBASE from inception through October 5, 2021, to identify randomized trials of Suanzaoren. We included randomized trials comparing Suanzaoren to placebo, medications, cognitive behavioral therapy (CBT), or usual care for improving sleep o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In this work, ziziphus jujuba spinosa kernel (Suan Zao Ren), polygala tenuifolia (Yuan Zhi), albizia julibrissin flower (He Huan Hua), polygonum multiflorum stem (Shou Wu Teng), schizandra chinensis (Wu Wei Zi), nelumbo nucifera seed (Lian Zi) and coptis chinensis (Huang Lian) are used as the TCM materials for the MN patch. Here, Suan Zao Ren is utilized to nourish the liver, calm the heart and nerves, and reduce the sweat [ 44 ]. Yuan Zhi is used to calm the nerves, promote the intelligence, dispel the phlegm, and reduce the swelling [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, ziziphus jujuba spinosa kernel (Suan Zao Ren), polygala tenuifolia (Yuan Zhi), albizia julibrissin flower (He Huan Hua), polygonum multiflorum stem (Shou Wu Teng), schizandra chinensis (Wu Wei Zi), nelumbo nucifera seed (Lian Zi) and coptis chinensis (Huang Lian) are used as the TCM materials for the MN patch. Here, Suan Zao Ren is utilized to nourish the liver, calm the heart and nerves, and reduce the sweat [ 44 ]. Yuan Zhi is used to calm the nerves, promote the intelligence, dispel the phlegm, and reduce the swelling [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The production process of the CHM related products mainly includes extraction, concentration, and drying. The active ingredients of these seven herbs can be extracted with alcohol, and the residue can be filtered effectively [ [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The resulting liquid is concentrated to remove excess water, and dried to obtain the powders.…”
Section: Methodsmentioning
confidence: 99%
“…The rapid pace of modern life, increased work pressure, and irregular sleep patterns have led to an increase in insomnia and significantly impacted people's daily lives [2]. SZS is commonly used to improve sleep [3]. Modern research has demonstrated that SZS contains flavonoids, triterpenoid saponins, alkaloids, fatty acids, and other compounds [4][5][6][7], which exhibit certain effects on preventing and treating insomnia.…”
Section: Introductionmentioning
confidence: 99%